Utilization of the Bacteria Bacillus pumilus and Citrobacter youngae as Flotation Bioreagents in the Microflotation of Chalcopyrite, Pyrite, and Silica (Indonesian Society for microbiology, 2016)
Until presently, relatively toxic and expensive chemical reageants are routinely used in the flotation of sulfide and oxide minerals. To establish a more environmentally friendly flotation process, alternative flotation reagents have been explored extensively by using microbes and their metabolic products such as biosurfactants or EPS (extracellular polymeric substances) as high molecular weight biosurfactants. Hence, the present work focused on the application of the mixotrophic bacteria capable of both producing biosurfactants and oxidizing iron-sulfur (herein Bacillus pumilus strain SKC-2 and Citrobacter youngae strain SKC-4) as flotation bioreagents in the microflotation of chalcopyrite, pyrite and silica. Laboratory microflotation tests using both bacterial strains as bioreagents were evaluated as a function of conditioning time, pH and bacterial cell concentration. Experimental evidence indicated that the chalcopyrite recoveries could be achived using both bacterial strains but its better recovery was obtained with the bacterium Citrobacter youngae as bioreagents. The findings of this study thus suggest the possible application of these bacterial strains as flotation bioreagents in order for establishing a more eco-friendly mineral processing.